Aspects of the sustainable utilization of renewable energy sources - Dombi, Mihály; Kuti, István; Balogh, Péter (Applied Studies in Agribusiness and Commerce, 2012)
The aim of this paper is to analyze the main approaches to sustainability and to present an alternative interpretation for the issues involved in the utilization of RES. The utilization technologies can be described by the average values of several technological parameters. Some significant parameters were chosen which are the most relevant for the issue of sustainability. The group of attributes was composed of these parameters in the analysis, which was conducted by the choice experiment (CE) methodology. The examination of each attributes’ influence on the individual’s preferences and choices was made possible by this method and the preferences of the relevant experts were determined. The weight of the attributes was defined by experts according to the importance of each attribute regarding RES-based technologies. The importance of sustainability attributes implies the significance of sustainability in the case of RES technologies, which thus highlights the characteristics of the more prosperous technological parameters regarding sustainable development.